Global partnership in Technical Vocational Education and Training (TVET) for curbing youth unemployment and restiveness in North-East, Nigeria - Wombo, Adoo Blessing (Journal of Professional Teacher Education, 2023)
The study was concerned with the techniques for curbing youth unemployment and restiveness through global partnership in Technical Vocational Education and Training for achieving sustainable development goals 2016-2030 in North-East Nigeria. As the survey research design was adopted, four specific objectives and four null hypotheses guided the study. The population of the study was 468 subjects, consisting of 282 Social workers and 186 Vocational guidance counselors in six states of the North-East geopolitical zone of Nigeria. The entire population was used as the sample for the study because of its small size. Data was collected using a structured questionnaire titled - Curbing Youth Unemployment and Restiveness through Global Partnership in Technical Vocational Education and Training Questionnaire (CYURGPTEVTQ), validated by three experts with a Cronbach alpha correlation coefficient of 0.88. The researchers and two research assistants administered the instrument. Mean, and Standard deviation was used to answer the research questions, while student t-test statistics were used to analyze the null hypotheses at a 0.05 level of significance (P = 0.05). The study showed that youth unemployment was the critical factor generating community restiveness. Based on the findings, jobs should be created, and youths should be equipped with relevant skills, attitudes, and knowledge through TVET to curb youth unemployment and restiveness.